'I think I preferred it abstract': Christine Brooke-Rose and visuality in the new novel. Issue 2 (7th February 2018) - Ferris, Natalie
ABSTRACT: In one of her earliest critical reviews, written for The London Magazine in December 1958, Christine Brooke-Rose began to stake out territory for new literary work that confounded most critical outlines. These works, which she deemed 'necessary to the development of the novel or play' and 'indispensable to our knowledge of the form', were to be contrasted with the mode traditionally associated with the novel, social realism, placed in opposition to the works of authors 'whose main concern is to tell a story about persons recognizable as human beings in recognizable situations'. As Brooke-Rose's literary career matured along with the dawning of the 1960s, following publication of her poetry pamphlet Gold (1954), a quartet of satirical novels (1957–1961) and her first scholarly work The Grammar of Metaphor (1958), Brooke-Rose's connection to the nouveau roman became the single most definitive characteristic in the eyes of her British readership. This essay will consider the influence of the main protagonists of the nouveau roman upon Brooke-Rose's short stories and novels, with particular attention paid to her novel Out (1964) and to the emphasis placed by the nouveau romanciers upon the visual and cinematic as the privileged means of apprehending reality.